2023
DOI: 10.1029/2022sw003219
|View full text |Cite
|
Sign up to set email alerts
|

The Ionospheric Dynamics of the African Sector Responding to a Severe Geomagnetic Storm; the Storm of 3–5 November 2021

Abstract: A geomagnetic storm is a disturbance on the Earth's magnetic field resulting from enhanced energy transfer from interplanetary space to the Earth's environment through the magnetosphere. The cause of geomagnetic storms is variation in the solar wind parameters, that is enhancement in solar wind speed and solar wind particles that increase solar wind pressure, and at least >3 hr sustained southward interplanetary magnetic field (IMF) on the day side magnetosphere (Gonzalez et al., 1994;Kumar & Kumar, 2019). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The SYM-H index exhibited two major negative peaks, which are −111 nT at 08:25 UT and −117 nT at 13:00 UT on 04 November, respectively. Several previous studies have reported that this geomagnetic storm triggered notable low-latitude ionospheric disturbances, especially over the South American sector (Rukundo, 2023;K. Wu et al, 2023;Zhai et al, 2022).…”
Section: Results and Validationmentioning
confidence: 85%
See 1 more Smart Citation
“…The SYM-H index exhibited two major negative peaks, which are −111 nT at 08:25 UT and −117 nT at 13:00 UT on 04 November, respectively. Several previous studies have reported that this geomagnetic storm triggered notable low-latitude ionospheric disturbances, especially over the South American sector (Rukundo, 2023;K. Wu et al, 2023;Zhai et al, 2022).…”
Section: Results and Validationmentioning
confidence: 85%
“…The SYM‐H index exhibited two major negative peaks, which are −111 nT at 08:25 UT and −117 nT at 13:00 UT on 04 November, respectively. Several previous studies have reported that this geomagnetic storm triggered notable low‐latitude ionospheric disturbances, especially over the South American sector (Rukundo, 2023; K. Wu et al., 2023; Zhai et al., 2022). This provides a good opportunity to assess our newly developed TIDAS‐SA regional data assimilation system and conduct an in‐depth analysis of the storm‐induced ionospheric perturbations.…”
Section: Results and Validationmentioning
confidence: 90%
“…On other days, a normal trend of diurnal EEJ is observed in the African sector with westward EEJ (CEJ effects) and eastward EEJ in the early morning and evening, respectively. In this context, Rukundo (2023) also studied the ionospheric dynamics of the African Sector in response to a severe geomagnetic storm of 3–4 November 2021. The African ionosphere responded to the storm with distinct features characterized by the equatorward traveling atmospheric disturbances and electric fields.…”
Section: Resultsmentioning
confidence: 99%
“…Rukundo (2023) used MIT‐based TEC to study temporal fluctuations in TEC across the African longitudinal sector. On November 3rd and 5th, separate EIA crests at approximately 15° on either side of the geomagnetic equator were observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation